PENGEMBANGAN BAHAN AJAR MATERI SIKLUS AIR BERBASIS PjBL BERBANTUAN VIDEO YOUTUBE UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR HOTS PESERTA DIDIK di KELAS IV SEKOLAH DASAR - Haryanti, Upin; Widi Winarni, Endang; Juarsa, Osa (UNIB Press, 2025)
The purpose of this study is to develop teaching materials for water cycle material based on Project Based Learning assisted by YouTube videos to improve HOTS thinking. The type of research used is Research and Development (R&D) research using the ADDIE model. The types of data used are quantitative and qualitative data, namely quantitative data using a questionnaire assessment score given by the validator while qualitative data is criticism and suggestions from expert validation. Based on the results of the study, it was obtained that the application of science learning using teaching materials for water cycle material based on the Project Based Learning model assisted by YouTube videos improves HOTS thinking. This is indicated by the results of the pretest and posttest assessments. HOTS thinking ability on the pretest results of analytical thinking (C4) was 38.25, evaluating thinking (C5) was 35.25 and creative thinking (C6) was 27.29. Meanwhile, the average posttest results of analytical thinking (C4) were 94.50, evaluating thinking (C5) was 90.33 and creative thinking (C6) was 94.50. The application of science learning by developing water cycle teaching materials based on Project Based Learning assisted by Youtube videos significantly increased HOTS thinking ability. This is indicated by the average pretest of HOTS thinking ability in the control class of 34 while the average posttest result was 93.